Influence of Molybdenum Addition on the Microstructure and the Subcritical Treatment Hardening Effect of High - Chromium Cast Iron - SI Song - hua, FANG Ji - ming, ZHANG Chi, XU Xiao - long, XU Ting, ZHANG Ao (Cailiao Baohu, 2021)
For improve the comprehension performance of high - chromium cast iron, the influences of Mo addition on the microstructure of as - cast high - chromium cast iron and the subcritical treatment effect at 550 ℃ on the microstructure and hardness of the as - cast high - chromium cast iron were studied with using the high - chromium cast irons with / without 1%(mass fraction) Mo as research objects. Results showed that the main constituent phases of the two kinds of as - cast high chromium cast iron are austenite, martensite and (Cr, Fe)7C3, but the content of austenite in the Mo - containing high chromium cast iron obviously increased. Meanwhile, the as - cast high - chromium cast iron crystallized in a hypoeutectic manner, and its microstructure was composed of primary dendritic solid solution and the eutectic microstructure between them. However, the dendritic microstructure of Mo - containing high - chromium cast iron was apparently refined. Both kinds of high - chromium cast iron hardened after subcritical treatment at 550 ℃ for different holding time. The peak hardness of Mo - containing high - chromium cast iron (50 HRC) was 31.6% higher than that of cast iron, while the peak hardness of high chromium cast iron without Mo (48 HRC) was 14.2% higher than that of cast iron. Moreover, the peak hardness time of high chromium cast iron containing Mo (15 h) was longer than that of high chromium cast iron without Mo (5 h). The addition of Mo element could refine the dendritic structure of high - chromium cast iron and improve the hardening effect after subcritical treatment.